PKRC Gambang as a show of solidarity for UMP to handle Covid 19 - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 1 June 2021 - The selection of the Universiti Malaysia Pahang (UMP) Sports Complex as the sixth Covid-19 Low-Risk Quarantine and Treatment Centre (PKRC) in the state is to accommodate more patients.